Peer Reviewed Evaluation of Registered End-Points of Randomised Trials (the PRE-REPORT study): a stepped wedge, cluster-randomised trial. Issue 9 (28th September 2022) - Jones, Christopher W; Adams, Amanda; Misemer, Benjamin S; Weaver, Mark A; Schroter, Sara; Khan, Hayat; Margolis, Benyamin; Schriger, David L; Platts-Mills, Timothy F
Abstract : Objective: To test whether providing relevant clinical trial registry information to peer reviewers evaluating trial manuscripts decreases discrepancies between registered and published trial outcomes. Design: Stepped wedge, cluster-randomised trial, with clusters comprised of eligible manuscripts submitted to each participating journal between 1 November 2018 and 31 October 2019. Setting: Thirteen medical journals. Participants: Manuscripts were eligible for inclusion if they were submitted to a participating journal during the study period, presented results from the primary analysis of a clinical trial, and were peer reviewed. Interventions: During the control phase, there were no changes to pre-existing peer review practices. After journals crossed over into the intervention phase, peer reviewers received a data sheet describing whether trials were registered, the initial registration and enrolment dates, and the registered primary outcome(s) when enrolment began. Main outcome measure: The presence of a clearly defined, prospectively registered primary outcome consistent with the primary outcome in the published trial manuscript, as determined by two independent outcome assessors. Results: We included 419 manuscripts (243 control and 176 intervention). Participating journals published 43% of control-phase manuscripts and 39% of intervention-phase manuscripts (model-estimated percentage difference between intervention and control trials = −10%, 95% CI −25% to 4%). Among the 173 accepted trials, published primary outcomes were consistent with clearly defined, prospectively registered primary outcomes in 40 of 105 (38%) control-phase trials and 27 of 68 (40%) intervention-phase trials. A linear mixed model did not show evidence of a statistically significant primary outcome effect from the intervention (estimated difference between intervention and control=−6% (90% CI −27% to 15%); one-sided p value=0.68). Conclusions: These results do not support use of the tested intervention as implemented here to increase agreement between prospectively registered and published trial outcomes. Other approaches are needed to improve the quality of outcome reporting of clinical trials. Trial registration number: ISRCTN41225307 .